Pemanfaatan Bokashi Jerami Padi Sebagai Sumber Hara Organik - Wan Arfiani Barus; Rizki Fadhillah Lubis (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
Utilization of agricultural waste as a source of nutrients, is one of the important things in the organic farming system. The organic farming system is a mainstay in realizing a sustainable agricultural system. One of the agricultural wastes that can be utilized is rice straw. This community service activity was held in Paluh Merbau Hamlet, Percut Sei Tuan, Deli Serdang, North Sumatra. The purpose of this community service is to provide direction and examples to farmers about the use of rice straw to be used as bokashi. Rice straw is one source of organic nutrients. Rice straw can be used in the form of compost and bokashi. Rice straw has very good nutrients to be used as organic fertilizer. The end result of this community service is farmers who are proficient in making bokashi rice straw.